PENGARUH ROA, DER DAN PER TERHADAP RETURN SAHAM PADA PERUSAHAAN CONSUMER GOODS INDUSTRY DI BURSA EFEK INDONESIA PERIODE 2010-2015 - Soedjatmiko -; Hilmi Abdullah; Ahmad Taufik (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2018)
Abstract, This research aims to prove empirically whether ROA, DER and PER effect on stock returns in the consumer goods industry firms in Indonesia Stock Exchange Period 2010-2015. This research method using quantitative methods. The population in this study is the industrial consumer goods company in Indonesia Stock Exchange (BEI) in 2010-2015 amounted to 31 companies. The sampling technique used in this research is purposive sampling. Samples were selected as many as 17 companies. Hypothesis testing results partially explain the ROA, DER and PER no effect on stock returns in the consumer goods industry firms in Indonesia Stock Exchange period 2010 - 2015. The results of hypothesis testing simultaneously explaining ROA, DER and PER no effect on stock returns in the consumer goods firms industry in Indonesia Stock Exchange Period 2010-2015.